2014
DOI: 10.1002/jbm.b.33134
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the bioactivity of polymeric implants by means of cold gas spray coatings

Abstract: Nanostructured anatase coatings were built-up on biocompatible polyetheretherketone (PEEK) by means of cold gas spray (CGS). Titanium layer was previously desposited, which acted as bond coat between PEEK and metal oxide. Semicrystalline polymer was not degraded during the spraying process and starting composition of titanium dioxide was not affected. TiO₂ was homogeneously obtained onto CGS Ti layer and completely covered the piece. Primary human osteoblasts were seeded onto biomaterials and in vitro cell exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…102,103 Moreover, nanostructured TiO2 may also be used as bioactive coatings. 109,293,294 Ag-SnO2 and Ag-Ni coatings can be used as industrial electrical contacts for contactors and circuit breakers. 101,104 Cu-CNTs composite coatings are used for boiling heat transfer.…”
Section: Functional Coatingsmentioning
confidence: 99%
“…102,103 Moreover, nanostructured TiO2 may also be used as bioactive coatings. 109,293,294 Ag-SnO2 and Ag-Ni coatings can be used as industrial electrical contacts for contactors and circuit breakers. 101,104 Cu-CNTs composite coatings are used for boiling heat transfer.…”
Section: Functional Coatingsmentioning
confidence: 99%
“…Another example of bond coat deposition by cold spraying was a FGC system deposited onto polymer substrate for biomedical applications [383]. The authors describe the bond coat of titanium produced on the biocompatible PEEK substrate.…”
Section: New Applications Of Fgcmentioning
confidence: 99%
“…It was also observed that Ti with biocompatible polymer implants can be successfully deposited resulting in homogenous, thick and good bond strength coating. Gardon et al (2014) investigated the behaviour of nano-structured anatase cold spray coating on polyetheretherketone biocompatible material. The result shows that depositing coating enhances the performance of polyetheretherketone implants.…”
Section: Biomedical Applicationmentioning
confidence: 99%